2021
DOI: 10.31579/2693-7247/033
|View full text |Cite
|
Sign up to set email alerts
|

Highlights on Chaetomium morphology, secondary metabolites and biological activates

Abstract: Endophytic fungi always attract attention due to their generous production of bioactive and chemically novel compounds that have medical, agriculture, industrial applications. This review focused on Chaetomium as a model of endophytic fungi rich in therapeutic agents that have known medicinal and industrial application. Moreover, understanding the importance of this potent fungus encourage further studies to identify novel metabolites, and at the same time employing already known metabolites to evaluate their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
4
1
Order By: Relevance
“…These compounds were identi ed as acetyl tributyl citrate (ATBC) at a concentration of 35.29%, 2,4-ditert-butylphrenol (2,4-DBP) at 13.4%, 1hexadecanol at 8.35%, 1-nonadecene at 5.67%, decanedioic acid, dibutyl ester at 4.4%, and 7-hexadecane at 4.18%. Consistent with the ndings of Elkhateeb et al (2021), the analysis of the crude extract of Chaetomium sp. by (GC-MS) revealed the presence of several compounds with bioactive properties, including antimicrobial and antioxidant compounds.…”
Section: Discussionsupporting
confidence: 83%
“…These compounds were identi ed as acetyl tributyl citrate (ATBC) at a concentration of 35.29%, 2,4-ditert-butylphrenol (2,4-DBP) at 13.4%, 1hexadecanol at 8.35%, 1-nonadecene at 5.67%, decanedioic acid, dibutyl ester at 4.4%, and 7-hexadecane at 4.18%. Consistent with the ndings of Elkhateeb et al (2021), the analysis of the crude extract of Chaetomium sp. by (GC-MS) revealed the presence of several compounds with bioactive properties, including antimicrobial and antioxidant compounds.…”
Section: Discussionsupporting
confidence: 83%
“…All previous studies indicate to significant ability of A. jodhpurensis in biological control of several plant pathogens besides its medical and industrial applications [39,40,41]. However, in the current study, A. jodhpurensis fungus was found to be pathogenic causing root rot disease on pepper plant.…”
Section: B Acontrasting
confidence: 61%
“…Over 200 compounds with a broad range of bioactive effects have been isolated from Chaetomium sp. so far (Table 1) (Elkhateeb et al 2021), yet more bioactive secondary metabolites can potentially be found.…”
Section: Introductionmentioning
confidence: 99%